The business aims of eight national libraries in digital library co-operation : a study carried out for the business plan of The European Library (TEL) project - Collier, Mel (2005)
Describes the process and results of the business-planning workplace of The European Library (TEL) project, in which eight national libraries collaborated on a joint approach to provide access to their digital libraries.